Hubungan Status Imunisasi dan ASI Esklusif Terhadap Kejadian Stunting Pada Anak Balita Usia 12 - 59 Bulan di Wilayah Kerja Puskesmas Sarageni Kabupaten Lebak - Nurkholiza, Hunafa; Widyastuti, Wiwin (Universitas Malahayati, 2025)
ABSTRACT Stunting is a chronic malnutrition problem caused by insufficient nutritional intake over a long period of time due to providing food that is not in accordance with nutritional needs. There are several factors that cause stunting, including immunization status and exclusive breastfeeding. To determine the relationship between immunization status and exclusive breastfeeding and the incidence of stunting in children under five aged 12-59 months in the working area of the Sarageni Health Center, Lebak Regency in 2024. This research is quantitative with a cross sectional approach. The sample in this study was 82 mothers who had toddlers aged 12-59 months in Jayasari Village, Sarageni Health Center Working Area, using a purposive sampling technique. The research results showed that there was a relationship between immunization status (p=0.003) and exclusive breastfeeding (p=0.003) with the incidence of stunting in children under five aged 12-59 months in the working area of the Sarageni Health Center, Lebak Regency in 2024. There is a relationship between immunization status and exclusive breastfeeding and the incidence of stunting in children under five aged 12-59 months in the working area of the Sarageni Health Center. It is hoped that the Sarangeni Community Health Center can provide education to the community about the importance of immunization and exclusive breastfeeding for children, either by gathering crowds at posyandu or visiting the homes of mothers who have babies/toddlers directly (door to door). There is a relationship between nutritional status and the incidence of anemia in pregnant women. Pregnant women are expected to increase their nutritional intake by consuming foods that contain iron such as heme in meat. If the mother is unable to consume it, it can be replaced with cheaper freshwater fish. Keywords: Immunization Status, Exclusive Breastfeeding, Stunting ABSTRAK Stunting merupakan masalah kurang gizi kronis yang diakibatkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Terdapat beberapa faktor penyebab dari kejadian stunting diantaranya yaitu status imunisasi dan ASI Ekslusif. Untuk mengetahui hubungan antara status imunisasi dan ASI Ekslusif dengan kejadian stunting pada anak balita usia 12-59 bulan di wilayah kerja Puskesmas Sarageni Kabupaten Lebak Tahun 2024. Penelitian ini bersifat kuantitatif dengan pendekatan cross sectional. Sampel dalam penelitian ini adalah Ibu yang memiliki balita usia 12-59 bulan di Desa Jayasari Wilayah Kerja Puskesmas Sarageni yaitu sebanyak 82 orang dengan teknik purposive sampling. Hasil penelitian di dapatkan bahwa ada hubungan status imunisasi (p=0,003) dan ASI Ekslusif (p=0,003) dengan kejadian stunting pada anak balita usia 12-59 bulan di wilayah kerja Puskesmas Sarageni Kabupaten Lebak Tahun 2024. Ada hubungan antara status imunisasi dan ASI Ekslusif dengan kejadian stunting pada anak balita usia 12-59 bulan di wilayah kerja Puskesmas Sarageni. Diharapkan pihak Puskesmas Sarangeni dapat melakukan penyuluhan kepada masyarakat tentang pentingnya imunisasi dan ASI Ekslusif bagi anak, baik dengan mengumpulkan massa di posyandu atau mendatangi rumah ibu yang mempunyai bayi/balita secara langsung (door to door). Kata Kunci: Status Imunisasi, Asi Ekslusif, Stunting